The Planning of Revetment For Coastal Protection of Candikusuma Jembrana Bali - Najmi Nurgitasari; Eko Pradjoko; Agus Suroso (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
Candikusuma Beach in Bali has experienced significant erosion since 2009, threatening public facilities, including a mosque in Candikusuma village. This issue is critical as it affects a coastal fishing community. To mitigate the erosion, a revetment structure using concrete block armor is proposed. This revetment aims to protect the coastal cliff from wave forces and prevent further erosion. The planning process begins with analyzing bathymetric and topographic data to assess land and sea conditions. Tidal analysis determines key water elevations, while wind data is used to calculate maximum and average wind speeds and directions. Wave hindcasting, based on wind data and effective fetch length, provides estimates of wave height and period. Shoreline changes are evaluated by comparing satellite imagery from 2003 and bathymetric surveys from 2012, revealing an average shoreline retreat of 21.70 meters over nine years. The design of the revetment includes a crest elevation of +3.70 meters MSL, constructed on a base at -0.5 meters MSL. The concrete foundation extends to a depth of -1.5 meters MSL. Hindcasting results show maximum wave heights of 1.21 to 1.50 meters from the southwest, with an average wave height of 0.01 to 0.30 meters from the south. The design wave height for a 25-year return period is 1.37 meters with a period of 4.58 seconds, resulting in a wave height of 1.31 meters at a depth of 2 meters. The estimated budget for the 200-meter-long revetment is Rp. 7,778,174,000.